Greek Students Research the Effects of Fire on the Soil System through Project-based Learning. Issue 3 (2nd July 2016) - Kioupi, Vasiliki; Arianoutsou, Margarita
Abstract : This study is focused on the development, implementation and evaluation of an environmental education programme for secondary education students. The programme was entitled 'Τhe effects of fire on the soil system' and it was implemented during the school period of 2008. Twenty-four (24) students (aged from 15 to 20) coming from Lidoriki Secondary School (Central Greece) participated in the programme, which was based on Project Method. The programme consisted of one theoretical part (achievement of cognitive and affective goals) and one experimental part (achievement of cognitive and psychomotor goals). Initial, formative and summative assessments were implemented during the course of the programme, by means of questionnaires, observation of students' teamwork and examination of their work sheets. The questionnaire analysis highlighted students' misconceptions regarding the subject, revealed positive changes in students' attitudes as a result of their participation in the programme, as well as satisfactory results concerning the acquired knowledge and skills. The experimental results were of significant scientific and educational value.